SOURCE STUDIES OF THE HISTORY OF SAMARKAND MADRASAHS (XVIII-XIX CENTURIES) (World Bulletin of Social Sciences, 2023)
It is known from history that madrasahs have long been famous as centers of knowledge, and at the same time as representatives of the local population, many foreign Taliban studied in madrasahs of Bukhara, Samarkand, and Gurganch cities. In these big cities, scientists interpreted works written in Indian, Persian, Greek, Arabic and other languages, wrote answers to them, and enriched world science and thinking. Rich libraries also functioned in these centers of knowledge. Today, thanks to the efforts of the head of the state and the leaders of the country, the history of existing madrasas in our country is studied, renovated and restored to its historical appearance. This will certainly help the growing young generations to strengthen their relationship with their ancestors, to follow in the footsteps of their ancestors, and to grow up to be great scientists and allama (fuzalo). Among the preserved madrasas in Samarkand, architectural monuments such as Ulugbek, Sherdar and Tillokori add beauty to the city.
Keywords: Madrasahs; school; mosque; house